Hubungan Sikap Mahasiswa Asrama Dengan Pencegahan Penularan Covid 19 Di STIKes Santa Elisabeth Medan 2022 - Vita Eskana Sihombing; Yanuarti Martina Putri (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2022)
Coronaviruses (CoV) are a large family of viruses that cause illness ranging from mild to severe. There are at least two types of coronavirus that are known to cause diseases that can cause severe symptoms such as Middle East Respiratory Syndrome (MERS) and Severe Acute Respiratory Syndrome (SARS). The purpose of this study was to determine the relationship between student dormitory attitudes and prevention of covid 19 transmission at STIKes Santa Elisabeth Medan 2022. The type of research design used in this study was a quantitative approach using a cross sectional design. The data used is primary data taken directly from the field using a questionnaire. The population in this study were students of D3 Nursing dormitory level 2 STIKes Santa Elisabeth Medan on June 18-20 July 2022 totaling 40 respondents, the sampling technique was carried out by total sampling. The location of the research was carried out in the Santa Elisabeth Medan STIKes dormitory on June 18-20 July 2022. The results of the chi-square statistical test on the relationship between student dormitory attitudes and prevention of covid 19 transmission at STIKes Santa Elisabeth Medan showed that from 40 respondents, a p-value = 0.004 was obtained. (p value> 0.05). Thus, the rejected results mean that there is a significant relationship between the attitudes of dormitory students and the prevention of covid 19 transmission at STIKes Santa Elisabeth Medan 2022. Where the majority of dormitory students with good attitudes have good prevention of covid transmission and dormitory students with poor attitudes have less prevention of transmission. . The results of the study can be seen that the prevention of covid transmission is not influenced by the attitude of the individual. For students, so that students can further increase their knowledge about COVID-19 and can implement attitudes and behaviors to prevent COVID-19 transmission in daily life